Mannitol versus hypertonic saline for intra-operative brain relaxation during aneurysm surgery - Sharma, Shalini; Grover, Vinod K.; Mathew, Preethy J. (Journal of Neuroanaesthesiology and Critical Care, 2015)
Background: The study was designed to compare the effects of equiosmolar and equivolemic 3% hypertonic saline (HTS) and 20% mannitol (M) on brain relaxation during aneurysm surgery. Materials and Methods: A prospective, randomised, double-blind study was undertaken in patients scheduled for surgical clipping of intracranial aneurysms presenting with Fisher grade I, II or III. The patients received either 300 mL of 3% hypertonic saline (HTS group) or 300 mL of 20% mannitol infusion (M group) during a period of 15 minutes at the start of scalp incision. The PaCO2 was maintained at 3.4-4.7 kilo Pascal, arterial blood pressure was maintained within ± 20% of baseline and central venous pressure was maintained at 5-10 cm of water. The haemodynamics, arterial blood gases and serum sodium concentration were compared. Surgeons assessed the condition of the brain as bulging, firm, satisfactorily relaxed and perfectly relaxed. An anaesthesiologist also assessed intra-operative brain relaxation. Results: The brain relaxation achieved with hypertonic saline was as good as that with mannitol. Urine output with mannitol was higher than with hypertonic saline (P < 0.04). Hypertonic saline caused an increase in serum sodium over one hour (P < 0.001) but resolved in 24 hours. Conclusions: The brain relaxation was equal in both the groups as assessed by the anaesthesiologist as well as the surgeon while the transient rise in serum sodium in hypertonic saline group returned to normal within 24 hours.
Keywords: Aneurysm surgery; hypertonic saline; mannitol